Risk factors associated with coronary artery disease at the Imam Ali Heart Centre, Kermenshah, West Iran - Berenjy, Shila (2012)
The present study was undertaken to determine risk factors of coronary artery disease (CAD). CAD is cause of half of the total death in Iran and metabolic syndrome (MS) is considered as a high prevalent risk factor of CAD. This case-control survey aimed to investigate the relationships between MS and lifestyle risk factors with coronary artery disease in patients with and without CAD undergoing angiography in Kermanshah Heart Center, West Iran This study also investigates the associations between various MS components such as triglyceride (TG), high-density lipoprotein (HDL), fasting blood sugar (FBS), blood pressure (BP), and waist circumference (WC) and selected lifestyle behaviors (dietary intake, physical activity patterns, and smoking habits) as the risk factors triggering and /or intensifying the development of CAD.Metabolic syndrome criteria were based on National Cholesterol Education Program/ Adult Treatment Panel, modified by American Heart Association / National Heart Lung & Blood Institute in 2005. Study data (including sociodemographic information, past medical history, dietary intakes, physical activity pattern, smoking habits, physical measurments and biochemical information) were collected through survey questionnaires, completed by the researcher in the presence of the patients. Quantitative data analysis techniques including paired samples t-test, conditional logistic regression (to quantify the Odds Ratio), chisquare, and multivariate modeling (to assess the effects of metabolic syndrome with and without adjustments) were done. The results showed significant differences between cases and controls in terms of their body mass index (BMI), WC, BP, TG, HDL-c, FBS and physical activity pattern. There were significant (p≤0.05) differences between the two groups in terms of their poly unsaturated fatty acids (PUFAs) and linoleic acid intake. The data from the present study indicated that sugar intake in the control group was significantly higher than that of the cases.The analysis showed statistically significant (p≤0.05) relationships between the level of education, occupation, and age at menopause and the risk of CAD. Data also showed that high sodium intake as well as high intake of dairy products, having previous history of high blood pressure and high blood glucose, high blood lipids, MS and all of its five components (abdominal obesity, low HDL-c, high TG and high FBS and high BP) and smoking increase the risk of CAD significantly (p≤0.05). Carbohydrate intake and physical activity (in all of three categories: sports, leisure time and work) decreased the risk of CAD significantly (p≤0.05). Almost all of the MS components were linked with risk factors of CAD and at least one MS component was present in all CAD patients. MS with all of five components increased the isk of CAD significantly more than thirteen times; additionally MS with minimum of three components increased the risk significantly more than four times. In addition, low HDL-c followed by high BP, abdominal obesity, high TG and high FBS had the highest CAD risk among the MS components in all patients. Hence, the most prevalent MS components in both CAD and non-CAD patients were high BP followed by low HDL-c and high TG, high FBS and abdominal obesity. Furthermore most of the patients with CAD had multi-vessel stenosis (grade III) which was the severest level of CAD. In conclusion low HDL-c and high FBS were positively and significantly related to first grade of CAD severity. Multivariate modeling was conducted to quantify the risk of CAD associated with metabolic syndrome after adjusting for other potential risk factors that were assessed in this study. Indeed in this study all the designed models show that MS is a significant predictor of CAD even in the presence of the other confounders and potentially CAD risk factors, however by adding MS components, MS conveyed no additional predictive information. Implications of these findings are useful for clinical practices as well as for general health practices. The results clearly show that early diagnosis of most MS components could delay or even is likely to deter the development of CAD in lower grades of CAD severity. Hence, implied in the finding is the fact that taking protective measures against the risks of CAD can greatly enhance the overall health standards of the society and reduce the mortality rates among the population.